(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The paper analyzes the errors and the causes of their occurrence in the construction of pits. A classification of accidents according to the costs of their liquidation has been developed. The importance of site surveys and the design process is emphasized, and some of the potential risks are outlined. The main causes of accidents are identified and recommendations are proposed to reduce the risks of their occurrence.